Salvation for the righteous revealed : Jesus amid covenantal and messianic expectations in Second Temple Judaism - Condra, Ed. (Arbeiten zur Geschichte des antiken Judentums und des Urchristentums, 2002)
Why is there such an ethical emphasis in Jesus' gospel proclamation? This work finds the answer in Jesus meeting his audience within their own conceptual realms and then expanding those realms to point to the nature of his salvation. The bulk of this work investigates the soteriology of Second Temple Judaism, especially of the Qumran Scrolls. The apocalyptic lesson was the demand of a greater covenantal obedience, held in tension with God's grace, a demand met through sectarian revelation and involving a somewhat diverse messianism. Within these conceptions, Jesus affirms that salvation is indeed for the "righteous," but as defined through himself as the unique Messiah. This work is particularly useful regarding the Jesus-Paul debate, for it provides a diachronic solution grounded in the cultural-historical milieu of the times.